The Implementation of Kid’s Athletics as an Interactive Audio Visual Learning Media - Hariadi, Hariadi; Suryansah, Suryansah; Watoni, Muhamad Rezeki Rizal (TEGAR: Journal of Teaching Physical Education in Elementary School, 2020)
This study was aimed at designing, creating, and developing an interactive audio visual learning media. This study was also aimed at examining the effectiveness of the implementation of the kid’s athletics interactive audio visual learning media on the student learning achievement. This research used a Research and Development method. The subjects of the study were 30 elementary students. The research design was the product development model. The data were analyzed by using a percentage calculation of the validation results. The validators were the expert in media and the expert in material. The result of the data analysis showed that the use of interactive audiovisual media kid’s athletics had been assessed as valid by the validators. The validity score was 85,71% from the media expert and 91,67% from the material expert. Therefore, the product was categorized as very good, which means it is applicable to use. The results of teacher instruction observation on using the kid’s athletics interactive audio visual media were 94,79% for the Kanga Escape material, 88,54% for Frog Jump material, 92, 70% for Turbo Throwing material, and 91,66 for Formula 1 material.